The use of suggestion in sports practice - Omelyanenko, V. I. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The aim of the study is to provide a comprehensive, integrated modified technique of personal psycho-physiological regulation based on a system of Raja Yoga. The study involved candidates and masters of sports of freestyle skiing in the amount of 21 people aged 17 to 23 years. Found that athletes co 2 and stage 3 of the hypnotic state successfully acquired by dhyana and can apply it in preparation for a competition. The proposed method includes a high quality optimal fighting condition, modeling and programming training and competitive processes using deferred units, the correction of motor skills. Athletes in their imagination run program of the second day of competition. Then, the third day of competition modeled, programmed overall health. Are told that in the day of the event will have a good mood, great feeling, a surge of strength, vigor, vitality, desire to show all of their sporting qualities.